Microporosity evolution and destruction in the Jurassic Arab D reservoir, Qatar - F. N. Sadooni (17726409) (2023)
Core samples were collected from three wells, one onshore and two offshore, from Qatar’s Upper Jurassic Arab D reservoir. The samples were subjected to multiproxy petrographic and chemical analyses to identify their micro- and nanoporosity types and understand their evolution and destruction. Based on the petrographic and petrophysical properties of studied rocks, the Arab D succession was divided into seven rock types. Primary microporosity includes intergranular and interplanar, while secondary types include vuggy, intercrystalline, moldic, dissolution, pyrite displacement, microfracture, and microbial boring. Primary micropores were found mainly between the micrite grains in the lime mudstone facies, between the grains or the plates of clay minerals. Secondary micropores result from open and closed diagenetic systems. The open diagenetic system led to the development of dissolution and moldic micropores, while the closed system created pyrite displacement and boring porosity. Mechanical stress due to crystal growth or displacement generated microfractures. Micropores were destroyed either by cementation, clay minerals growth, dolomitization, or microbial pustular overgrowth. Microporosity was important in quantity and varied in nature in the mud-supported rocks. They are similar to macropores in grain-supported sediments but of less importance. The complex lithology of the studied rocks has significantly influenced the development and destruction of the porosity system of the Arab Formation. Other Information Published in: Carbonates and Evaporites License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s13146-023-00869-7